Reducing cost by using a smaller instrument tray in hand surgery. Issue 6 (November 2018) - Kirn, Philip T.; Angermeier, Eric; Kokko, Kyle P.
Abstract : Background: The cost of US healthcare continues to rise at an unsustainable rate. A significant amount of waste occurs in the operating room. One way to reduce cost is by using trays with fewer instruments. The purpose of our study was to determine the cost to sterilize and process an instrument at our institution and calculate the expected savings when using a smaller tray for selected hand procedures. Methods: This was a single-site, observational study conducted at an academic medical center. The cost to sterilize an instrument was determined by dividing relevant labor and operating expenses by the total number of instruments processed. The ambulatory hand set was decreased from 105 to 16 instruments. Using the calculated cost to process an instrument, we determined cost savings per tray. By multiplying this value with the total number of cases for which the new tray would be used, we were able to determine expected cost savings per year. We also surveyed operating room staff with regards to work flow and satisfaction with the smaller tray. Results: Using the observed time to decontaminate and package an instrument, the labor cost was calculated to be 0.14 per instrument. The cost increased to 0.60 per instrument after including operating expenses. Decreasing the hand tray in selected procedures was calculated to save 31, 500 per year. The smaller tray resulted in improved work flow and high satisfaction scores among operating room staff. Conclusions: Our calculated expense to sterilize and process an instrument is similar to prior studies. Processing fewer instruments in selected hand procedures is expected to result in significant cost savings and improvement in operating room workflow and satisfaction.